Genetic diversity and relationship among three goat breed of Maharashtra state of India - KURALKAR, S V; KURALKAR, PRAJAKTA; KHARKAR, KRANTI (The Indian Journal of Animal Sciences, 2016)
Genetic diversity and relationship among in the three goat breed of Maharashtra, India namely Berari, Osmanabadi and Sangamneri were evaluated based on 25 microsatellite markers. A total of 567 alleles were observed among 129 assayed animals across the three breeds. The most diverse breed was Sangamneri followed by Berari and the least diverse breed was Osmanabadi in terms of number of allele. The overall mean of gene diversity across the studied loci for the Berari, Osmanabadi and Sangamneri breeds were 0.906±0.006, 0.870±0.017 and 0.901±0.010, respectively. The overall Fis value (0.161) was higher and significantly different from zero indicating departure from random mating and suggested that some of the studied loci were homozygous in the populations. The lower level of genetic differentiation (Fst) among the three breeds (3.9%) under study implied that 96.1% of the total genetic variation corresponded to differences among individuals within breed. The genetic distance tended to be the least (0.4032) between Berari and Sangamneri, moderate (0.4834) between Sangamneri and Osmanabadi and the widest (0.6319) between Berari and Osmanabadi. Lower level of genetic differentiation among the three breeds showed intermixing of the populations as breeding tract of three bred overlap hence, this may pose a danger to the purity of the breed in the long run.